European radon abatement policy: state and ongoing discussion - Peter Bossew; Nils Suhr (Brazilian Journal of Radiation Sciences)
Radon is a hazardous air pollutant which can cause detriment to individuals and to the society. Thus, the natural consequence is avoiding it or in practice, limiting exposure. This has led to regulation on national and international level whose objective is reduction of radon exposure. In Europe, the Basic Safety Standards (BSS) issued in 2013, whose implementation is mandatory for EU Member States, caused a boost to efforts towards radon regulation as well as to radon research since a number of components of radon abatement policy appeared not resolved sufficiently reliable in the sense of quality assurance. In this contribution, we present the state of implementation of EURATOM Basic Safety Standards in Europe and in Germany, as a particular example. We also address a number of topics currently discussed.